Interpreters and language assessment: confrontation naming and interpreting - Kambanaros, Maria; Van Steenbrugge, Willem (My University, 2004)
There has been an increase in issues regarding the involvement of interpreters in the assessment of language disorders in bilingual individuals. Most publications focus on overall issues, such as the respective roles of the speech pathologist and interpreter, the need for teamwork, the need to share information about the assessment methods and materials used, and the need for a three stage process of briefing, interaction and debriefing. The current article stresses the need for speech pathologists to share more of their professional knowledge with the interpreter, specifically knowledge about typical responses and behaviours of clients that form essential data or evidence in the diagnosis of a particular disorder, for example bilingual aphasia. This point is illustrated by a small case study of translated responses of a bilingual individual with aphasia during confrontation naming in the native language.
Keywords: Language disorders; Bilingual individuals; Aphasia; Native language